Exploiting the Irish Border to Estimate Minimum Wage Impacts in Northern Ireland - Duncan McVicar; Andrew Park; Seamus McGuinness (Institute of Labor Economics (IZA), 2018)
This paper examines employment and hours impacts of the 1999 introduction of the UK National Minimum Wage (NMW) and the 2016 introduction of the UK National Living Wage (NLW) in Northern Ireland (NI). NI is the only part of the UK with a land border where the NMW and NLW cover those working on one side of the border (NI) but not those working on the other side of the border (Republic of Ireland). This discontinuity in minimum wage coverage enables a research design that estimates the impacts of the NMW and NLW on employment and hours worked using difference-in-differences. We find a small decrease in the employment rate of 22-59/64 year olds in NI, of up to two percentage points, in the year following the introduction of the NMW, but no impact on hours worked. We find no evidence that the introduction of the NLW impacted either employment or hours worked in NI.
Keywords: E24; J31; J38; 330; minimum wages; Northern Ireland; employment; hours